Approved and Emerging Hormone-Based Anti-Obesity Medications: A Review Article - Wael R. Sidrak; Sanjay Kalra; Atul Kalhan (Indian Journal of Endocrinology and Metabolism)
Obesity is a heterogeneous, complex, and chronic disease that has a detrimental impact on disability-adjusted life years across the globe. Recent advancements in our understanding of gut-brain communication at the molecular level have driven the development of next-generation anti-obesity medications (AOMs). Glucagon-like peptide-1 receptor agonists (GLP1RAs) remain the front-runners in this rapidly evolving landscape of hormone-based AOMs. Two GLP1RAs, namely Liraglutide and Semaglutide, have been approved by the Food and Drug Administration (FDA) and European Medicine Agency (EMA) for use in clinical practice for weight loss. Three oral GLP1RAs, namely Semaglutide, Danuglipron, and Orforglipron, are undergoing advanced clinical trials in individuals with obesity. Amylin receptor agonist (AMYRA) Cagrilintide, when used alone or in combination with Semaglutide, has demonstrated substantial weight reduction in clinical trials. Tirzepatide, a dual agonist for the glucose-dependent insulinotropic polypeptide (GIP) and GLP-1 receptors, has been observed to be associated with a significant placebo-subtracted weight reduction of 17.8% in a 72-week randomized controlled trial. Novel approaches targeting glucagon signalling have also yielded promising preliminary results. Three long-acting GLP1R/glucagon receptor (GCGR) dual agonists, namely Survodutide, Mazdutide, and Pemvidutide, exhibited significant weight loss in clinical trials. Retatrutide, a GLP1R/GCGR/GIPR tri-agonist, has been associated with a placebo-subtracted weight reduction of -22.1% in a 48-week phase-II trial. As a note of caution, long-term data on such medications’ safety and cardiovascular benefits is yet to be ascertained. Our review provides a comprehensive overview of the approved and emerging hormone-based AOMs, highlighting the diversity of options that might become available in the near future.